2018
DOI: 10.1007/s10815-018-1342-y
|View full text |Cite
|
Sign up to set email alerts
|

Altered three-dimensional organization of sperm genome in DPY19L2-deficient globozoospermic patients

Abstract: To explore the three-dimensional (3D) organization of sperm genome in DPY19L2-deficient globozoospermic patients speculating a link between DPY19L2 and genome organization of sperm nucleus. Methods This is a study of chromatin organization in DPY19L2-deficient globozoospermic patients and healthy donors using threedimensional fluorescence in situ hybridization (3D-FISH) combined with confocal laser scanning microscopy followed by 3D image analysis. The 3D structures of sperm nuclei, chromocenter, telomeric reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Heterochromatic compartments play a significant role in the nucleus content [ 119 ]. However, gene mutations and chromatin and chromosomal rearrangements can change the intranuclear organization, which can lead to diseases and the appearance of various abnormal manifestations [ 120 , 121 , 122 , 123 , 124 , 125 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heterochromatic compartments play a significant role in the nucleus content [ 119 ]. However, gene mutations and chromatin and chromosomal rearrangements can change the intranuclear organization, which can lead to diseases and the appearance of various abnormal manifestations [ 120 , 121 , 122 , 123 , 124 , 125 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported perturbations, albeit often modest alterations in the positioning of various target loci. Alterations have been reported in patients exhibiting semen parameter disturbances and/or increased sperm aneuploidy [15,19,56,57], increased levels of DNA damage or nuclear perturbations such as sperm nuclear vacuoles [58,59], or carriers of chromosome translocations [45]. There are also inherent methodological differences between studies.…”
Section: Discussionmentioning
confidence: 99%
“…A handful of studies have reported mild to moderate alterations in chromatin organization in the sperm from various patient cohorts including: men with reduced/altered semen parameters, carriers of structural chromosome aberrations, increased sperm aneuploidy and DNA fragmentation etc. [15,19,45,56,57,58,59]. However, these studies are restricted to small numbers of patients and cells.…”
Section: Discussionmentioning
confidence: 99%
“…As sufferers are routinely screened for DPY19L2 deletion in this centre and according to a recent report by Ghazavi et al (), it has been suggested that embryos derived from couples in consanguineous marriages with globozoospermia should be screened for gender or DPY19L2 deletion in order to decrease the occurrence of globozoospermia in future progeny. Recent findings have clarified that DPY19L2 might have a key role in nuclear chromatin organisation in the sperm nucleus via its interaction with the nuclear lamina (NL) (Abdelhedi et al, ). The impact of the NL and its associated proteins during human spermiogenesis has been emphasised (Paci et al, ).…”
Section: Genetic Featuresmentioning
confidence: 99%